PENGARUH POLITICAL MARKETING MIX DAN VIRAL MARKETING TERHADAP KEPUTUSAN MAHASISWA DALAM MEMILIH GUBERNUR KALIMANTAN BARAT PERIODE 2018-2023 - B1021151052, Dwi Prastiyo (Jurnal Manajemen Update, 2019)
The purpose of this study is to determine and analyze the effect of political marketing mix (product, price, promotion, place) and viral marketing to College student’s decision on Voting West Borneo’s Governor 2018-2023 period. This research is a causal quantitative research. Population on this research is college student who has suffrage on West Borneo’s Governor Election 2018-2023 period. This research used purposive sampling technique with 150 samples. Data were collected by questionnaire method with likert scale 1 until 5. The analysis method used multiple linier regression analysis using SPSS V.23.0 software. The result showed that product, price and viral marketing have positive and significant effect, but promotion and place don’t have significant effect on College student’s voting decision on West Borneo’s Governor Election 2018-2023 period. For the next research, researcher hope and suggest to add other variables that have not yet include in this research.Keywords: Political marketing mix, viral marketing, voting decision.    DAFTAR PUSTAKAAlie, Marzuki. (2013). Pemasaran Politik Di Era Multi Partai. Jakarta: Ekspose.Amir, M. Taufiq. (2005). Dinamika Pemasaran: Jelajahi & Rasakan. Jakarta: Raja Grafindo Persada.Azwar, Saifuddin. (2010). Metode Penelitian. Yogyakarta: Pustaka Pelajar.Bauer, Hans H. (1996). Political Marketing: An Information-Economic Analysis. European Journal of Marketing, 30 (10-11), 152-165.Buchari, Alma. (2011). Manajemen Pemasaran dan Pemasaran Jasa. Bandung: Alfabeta.Dajan, Anto. (1996). Pengantar Metode Statistik Jilid II. Cetakan kedelapanbelas. Jakarta: Penertbit LP3ES.Ferdinand, Augusty. (2006). Metode Penelitian Manajemen. Semarang: Universitas Diponegoro.Firmanzah. (2012). Marketing Politik: Antara Pemahaman dan Realitas. Jakarta: Yayasan Obor Indonesia.Ghozali, Imam. (2013). Aplikasi Analisis Multivariate dengan program IBM SPSS 21 Update PLS Regresi. Semarang: Universitas Diponegoro.Harris, Phil. (2001). To Spin or Not to Spin That is The Question, The Emergence of Modern Political Marketing. The Marketing Review 2, 35-53.Hasan, Ali. (2010). Marketing. Yogyakarta: Media Presindo.Hurlock, E.B. (1991). Psikologi Perkembangan Suatu Pendekatan Sepanjang Rentang Kehidupan (Terjemahan oleh Istiwidayanti dan Soedjarwo). Jakarta: Erlangga.Ikhsan, Ridho Bramulya dan Saggaff Shihab, Muchsin. (2010). Pengaruh Marketing Mix dan Pengaruhnya Terhadap Keputusan Mahasiswa Universitas Lampung. Jurnal Manajeman dan Bisnis Sriwijaya, 08 (16).Kaplan, A. M. Haenlein, M. (2011). Two Hearts in Three-Quarter Time: How to Waltz The Social Media/Viral Marketing Dance. Business Horizons, (54), 253-263.Kotler, Phillip. (2004). Manajemen Pemasaran (edisi Bahasa Indonesia). Jakarta: PT Prenhalindo Indonesia.Kotler, Phillip dan Gary Amstrong. (2008). Dasar-Dasar Pemasaran. Alih Bahasa Alexander Sindoro, Penyunting Bahasa Bambang Sarwiji. Edisi Kesembilan. Jakarta: PT. Index.Kotler, Phillip dan Kevin L. Keller. (2009). Manajemen Pemasaran. Alih Bahasa Benyamin Mollan. Edisi Keduabelas. Jakarta: PT. Macanan Jaya Cemerlang.Kuncoro, Mudrajad. (2011). Metode Kuantitatif: Teori dan Aplikasi Untuk Bisnis & Ekonomi. Yogyakarta: Sekolah Tinggi Ilmu Manajemen YKPN.Lupiyohadi. (2001). Manajemen Pemasaran Jasa: Teori dan Praktek. Jakarta: Salemba Empat.Marland, Alex dan Thierry Giasson. (2013). Investigating Political Marketing Using Mixed Method: The Case for Campaign Spending Data. Journal of Public Affairs, 13 (4), 391–402.Niffenegger. (1989). Strategies for Success From The Political Marketers. Journal of Services Marketing, 2, 15-21.Pemilihan umum Gubernur Kalimantan Barat 2018. Diakses dari https://id.wikipedia.org/wiki/Pemilihan_umum_Gubernur_Kalimantan_Barat_2018Purba, Rikki Surria. (2016). Pengaruh Viral Marketing Melalui Aplikasi Line Terhadap Keputusan Pembelian (Studi Kasus Mahasiswa Telkom University pada Tahun 2016), e-Proceeding of Applied Science, 2 (2).Puspitaningtyas. (2014). PERAN KONSULTAN POLITIK DALAM PILKADA Strategi Marketing Politik PolMark Indonesia dalam Memenangkan Joko Widodo-Basuki Tjahaja Purnama pada Pilkada Provinsi DKI Jakarta 2012. Skripsi thesis, UNIVERSITAS AIRLANGGA.Putra, Yanuar Surya. (2016). Theoritical Review: Teori Perbedaan Generasi.  Jurnal Among Makarti, 9 (18), 123-134.Priyatno, Duwi. (2014). SPSS 22 Pengolah Data Terpraktis. Yogyakarta: ANDIPratama, Restu Dwi. (2015). Pengaruh political marketing mix terhadap keputusan memilih mahasiswa dalam pemilihan umum calon presiden dan calon wakil presiden 2014. Skripsi UIN Syarif Hidayatullah Jakarta.Ristania, Novia & Jerry S. J. (2013). Analisa Pengaruh Harga, Promosi Dan Viral Marketing Terhadap Keputusan Pembelian Pada "Online Shop" S-Nexian Melalui Facebook, Journal of Business Strategy and Execution, 5 (2), 131-161.Sekaran, Uma., &Bougie, R. (2017). Metode Penelitian untuk Bisnis. Jakarta: Salemba Empat.Setiyawan, Hari. (2017). Analisis Pengaruh Political Marketing Mix (Bauran Pemasaran Politik) Terhadap Keputusan Masyarakat Kota Pontianak Memilih Wali Kota Pontianak Periode 2013-2018. Jurnal Mahasiswa Manajemen, 6 (2).Selamat Tinggal Generasi Milenial, Selamat Datang Generasi Z. Retrieved from https://tirto.id/selamat-tinggal-generasi-milenial-selamat-datang-generasi-z-cnzXSiregar, Reiza J. (2019). Analisis Kemenangan Donald Trump Dalam Pemilihan Presiden Amerika Serikat Tahun 2016 (Figur Politik Donald Trump). Skripsi Reporsitori Institusi USU. Universitas Sumatera Utara.Shaughnessy. (2001). The Marketing of Political Marketing, European Journal of Marketing, 35 (9-10), 1047-1057.Situmorang, James. R. (2010). Pemasaran Viral. Jurnal Administrasi Bisnis, 6 (1), 59-71.Solimun et al. (2017). Metode Statistika Multivariat: Pemodelan Persamaan Struktural (SEM). Malang: UB Press.Stanton, William J. (2012). Prinsip Pemasaran. Jakarta: Erlangga.Strauss, William; Howe, Neil (2000). Millennials Rising: The Next Great Generation. New York, NY: Vintage Original.Sugiyono. (2008). Metode Penelitian Bisnis. Bandung:  Alfabeta.Sugiyono. (2009). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Sugiyono. (2017). Metode Penelitian Bisnis: Pendekatan Kuantitatif, Kualitatif, Kombinasi, dan R&D. Bandung: AlfabetaSunyoto, Danang. (2011). Metode Penelitian Ekonomi: Alat Statistik & Analisis Output Komputer untuk Mahasiswa dan Praktisi. Yogyakarta: Caps.Swasta, Basu dan Hani Handoko. (2008). Manajemen Pemasaran: Analisis Perilaku Konsumen. Yogyakarta: Universitas Gadjah Mada.Usia Produktif Mendominasi Pengguna Internet. Retrieved from https://databoks.katadata.co.id/datapublish/2018/02/23/usia-produktif-mendominasi-pengguna-internet.Williams, Christine B. (2017). Introduction: Social Media, Political Marketing and the 2016 U.S. Election. Journal of Political Marketing, doi: 10.1080/15377857.2017.1345828.Wring, D. (1996). Political marketing and Party development in Britain: a `secret' history. European Journal of Marketing, 30 (10-11), 92-103.Wring, D. (1997). Reconciling Marketing with Political Science, Theories of Political Marketing. Journal of Marketing Management, 13, 651-663.